Analisis Uji Muatan Bijih Nikel (Nickel Ore) Berdasarkan IMSBC Code untuk Mencegah Liquefaction di Kapal Curah MV. RIZABEY - Rangga Surya Adi Setya; Ari Sriantini; Nyoman Ardiana Listriyawati (KAMPUS AKADEMIK PUBLISING, 2026)
Nickel ore is a Group A solid bulk cargo that can undergo liquefaction if the actual moisture content (MC) exceeds the transportable moisture limit (TML). Such conditions can trigger cargo shift, free surface effect, reduction in metacentric height, and loss of ship stability. This study aims to analyze the implementation of nickel ore cargo testing based on the International Maritime Solid Bulk Cargoes (IMSBC) Code aboard MV. RIZABEY, identify operational constraints, and evaluate the effectiveness of its implementation in preventing liquefaction. The research employs a qualitative descriptive approach through observations during sea practice from 30 October 2023 to 5 May 2024, interviews with the Master, Chief Officer, and surveyor, as well as document examination and documentation of loading activities. The results show that risk control is carried out through verification of cargo declaration, MC certificate, TML and flow moisture point (FMP), visual inspection, sampling, can test on each barge, weather monitoring, suspension of loading during rain, and monitoring of cargo condition in cargo holds. This implementation has provided important preventive layers, but has not been fully ideal because the vessel does not have quantitative testing equipment to verify MC and FMP, there is potential discrepancy between the shipper's documents and the actual cargo condition, weather changes can increase moisture content after testing, and operational pressure may influence loading decisions. The effectiveness of prevention depends on the validity of certificates, sample representativeness, the Master's firmness, and continuous monitoring. The study recommends independent laboratory verification, documented cargo refusal procedures, and strengthening coordination between the vessel, shipper, surveyor, and terminal.